2011
DOI: 10.1093/neuonc/nor052
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of primary brain tumor incidence in Australia (2000–2008)

Abstract: There are conflicting reports from Europe and North America regarding trends in the incidence of primary brain tumor, whereas the incidence of primary brain tumors in Australia is currently unknown. We aimed to determine the incidence in Australia with age-, sex-, and benign-versus-malignant histology-specific analyses. A multicenter study was performed in the state of New South Wales (NSW) and the Australian Capital Territory (ACT), which has a combined population of >7 million with >97% rate of population re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 18 publications
5
37
2
1
Order By: Relevance
“…In Saskatchewan, between 1970 to 2001, the incidence of primary brain tumors was 11.1 per 100,000 persons: 12.5 for males and 9.8 for females (Pirouzmand and Sadanand, 2007). In registries of Australia from 2000 to 2008 the overall incidence of primary brain tumors was 11.3 per 100,000 person-years (Dobes et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Saskatchewan, between 1970 to 2001, the incidence of primary brain tumors was 11.1 per 100,000 persons: 12.5 for males and 9.8 for females (Pirouzmand and Sadanand, 2007). In registries of Australia from 2000 to 2008 the overall incidence of primary brain tumors was 11.3 per 100,000 person-years (Dobes et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The highest rates of incidence are seen in North America, Australia (Dobes et al, 2011), and Western Europe, (Deltour et al, 2009) and the lowest incidences are reported in Asia, Central and South American regions (Ferlay et al, 2010). The GLOBOCAN 2008 study published in 2010, estimated the highest incidence of primary brain tumors in North Europe, and the lowest incidence in Eastern Africa (Ferlay et al, 2010).…”
Section: 3979 Epidemiology Of Primary Cns Tumors Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the incidence rate of primary brain tumors is higher in developed countries than that in developing nations [4]. It has been postulated that these differences could be in part related to the economy of the country, as the highest incidence rates are observed in Western Europe, North America and Australia [22,23], whereas the lowest rates are registered in Eastern Africa [24]. Nevertheless, differences in the CIRs of brain tumors between developed and developing countries could also be partially attributed to differences in the age distribution between countries as the incidence rate of most brain tumors gradually increases with age.…”
Section: Discussionmentioning
confidence: 99%
“…In Osaka, Japan, rates at ages 20–74 increased from 1975 to 1988, and at ages 75+ increased until 1984, but then stabilised; these changes were attributed to diagnostic improvements 11 . A recent study in Australia based on clinical data showed some increases 12,13 . No increases were seen from 1986 to 1998 in a previous study in New Zealand (NZ) 14 .…”
mentioning
confidence: 91%